The art of keeping cool - Lisle, Janet Taylor (New York Scholastic, 2000)
In 1942, Robert and his cousin Elliot uncover long-hidden family secrets while staying in their grandparents' Rhode Island town, where they also become involved with a German artist who is suspected of being a spy.
Keywords: World War, 1939-1945 -- Rhode Island -- Juvenile fiction; World War, 1939-1945 -- United States -- Fiction; Family problems -- Fiction; Artists -- Fiction; Cousins -- Fiction; Grandparents -- Fiction; Rhode Island -- Fiction